Effect of Shared Decision-making on Anxiety of Women Recommended for Prenatal Screening Tests in Southeast of Iran - Zahra Moudi; Raheleh Jam; Hossein Ansari; Mostafa Montazer Zohour (Tehran University of Medical Sciences, 2020)
Objective: To study the effect of shared decision-making (SDM) on the anxiety of women who were recommended for prenatal screening tests. Materials and methods: This quasi-experimental study was conducted on a total of 200 pregnant women who referred to the health centers of Zahedan, Iran, for prenatal care within April 7 to September 7, 2019. The control group received routine care, and the intervention group attended a session based on SDM. The demographic characteristics form and Spielberger Six-item State-Trait Anxiety Inventory were filled out before and immediately after the counseling, as well as before receiving the results of maternal serum biochemical markers. Results: No statistically significant effect of SDM on anxiety was reported between the control and intervention groups immediately after the counseling session (P=0.46). However, the obtained data showed that the mean value of anxiety scores (16.52±3.06) was higher among the women in the intervention group than that reported for the control group (13.80±3.55) on the day before receiving the results of the blood tests (P<0.001). Nevertheless, logistic regression analysis showed only women with a university level of education were likely to have higher anxiety scores than women with lower educational levels (AOR=10.60; 95% CI: 2.07-54.24; P=0.005). Conclusion: Offering prenatal screening can cause a slight increase in the level of anxiety among women with a university level of education. Therefore, it is required to implement supportive strategies to help high-risk pregnant women in coping with anxiety.